The Moderation Effects of Comparative Thinking Between Gratitude and Negative Affect During the COVID-19 Outbreak - Bernabe-Valero, Gloria; Blasco-Magraner, José Salvador; Aguilar-Moya, Remedios; Moret-Tatay, Carmen (Frontiers in Psychology, 2021)
The aim of this research was to examine the moderation effects of comparative thinking (CT) across the relationship between gratitude and affect during the COVID-19 outbreak. To this purpose, multiple regression as well as moderation analyses were carried out. Age and sex were also addressed as variables of interest as described in previous literature. A sample of 306 north Americans was recruited by crowdsourcing platform ProA to obtain a representative sample based on age and gender. The participants filled in a questionnaire based on comparative thinking in relation to the emotional experience experienced before and during the COVID-19 outbreak, positive and negative affect schedule for positive and negative affect, as well as Gratitude Questionnaire - Six Items Form scores for gratitude. The main results of the current study related to the COVID-19 outbreak can be listed as follows: (i) no differences between CT groups in the gratitude trait, but differences in positive and negative affect did occur; (ii) regression models that included age, gratitude, and affect variables predicted negative and positive affects but gender did not reach the statistical level; (iii) two moderation models predicted affect from gratitude, with the CT variable moderating this effect; this moderation effect was also statistically significant in predicting negative affect but it was not statistically significant in predicting positive affect. These results might be of interest for training programs in applied levels and theoretical models of gratitude.